A kind of wrinkled stainless steel color-coated plate
By adopting paint components and process treatment with specific ratios, the problem of wrinkled stainless steel colored plates being easily worn during use is solved, which significantly improves the wear resistance and adhesion of the paint and extends the service life.
Patent Information
- Application Number
- CN202311420581.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The existing wrinkled stainless steel colored plates are easily affected by external wear or scratches during use, which will affect the appearance effect and service life.
Wrinkle coatings composed of polyester resin, titanium dioxide, wrinkle agent, rosin resin, modified bentonite, modified glass fiber, triglycidyl isocyanurate, microcrystalline wax powder and pigments are used to improve the wear resistance, adhesion and mechanical properties of the coating through specific ratios and processes.
It significantly improves the wear resistance, durability and adhesion of wrinkled stainless steel colored plates, extends service life, and enhances the mechanical properties and scratch resistance of the paint.
Smart Images

Figure BDA0004520970810000081 
Figure BDA0004520970810000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of plates, and in particular to a corrugated stainless steel color-coated plate. Background Art
[0002] Color-coated stainless steel sheets, also known as color-coated stainless steel sheets, use stainless steel as the base material. The surface is chemically treated and coated with an organic coating to obtain a sheet with high corrosion resistance and high strength. It is widely used in architectural decoration, electrical appliance manufacturing, transportation and other fields.
[0003] Wrinkle paint is a paint that can form wrinkles. It is usually composed of amino resin, pigment, alkyd resin, etc. The surface looks like the pattern left by hammering iron plate. It is tough and durable, with harmonious colors and beautiful patterns. Applying wrinkle paint on stainless steel substrates can achieve the functional diversity and variety of stainless steel, which is very popular among people.
[0004] However, in the prior art, when the corrugated stainless steel color plate is used, it will be worn or scratched by external force, which will affect the appearance and service life of the stainless steel color plate. Summary of the invention
[0005] In order to improve the problem of wear or scratching on the surface of a corrugated stainless steel color plate, the present application provides a corrugated stainless steel color-coated plate.
[0006] The present application provides a corrugated stainless steel color-coated plate, which adopts the following technical solution:
[0007] A wrinkle stainless steel color-coated plate, comprising a steel plate substrate and a wrinkle coating, wherein the wrinkle coating comprises the following raw materials, by weight: 40-50 parts of polyester resin, 12-20 parts of titanium dioxide, 1-3 parts of wrinkle agent, 3-5 parts of rosin resin, 10-15 parts of modified bentonite, 8-15 parts of modified glass fiber, 6-10 parts of triglycidyl isocyanurate, and 20-30 parts of microcrystalline wax powder
[0008] And 1-2 parts of pigment.
[0009] By adopting the above technical scheme, the polyester resin has good mechanical properties, excellent wear resistance, heat resistance, weather resistance and chemical resistance, the titanium dioxide has good chemical stability, light stability, wear resistance and resilience, and can improve the hiding power, durability, hardness and wear resistance of the coating. The wrinkle agent is an auxiliary agent that changes the surface tension of the molten coating when the coating is melted, leveled and solidified into a film, so that the coating shrinks and produces wrinkles or orange peels; the rosin resin can increase the viscosity, flexibility and wear resistance of the coating, prevent the coating from falling off and peeling during use, and increase the durability of the coating; triglycidyl isocyanurate can effectively accelerate the drying speed of the coating, increase the curing time of the coating, and make the coating and the steel plate substrate bond better.
[0010] Modified bentonite can improve the suspension stability of the coating system, not only increasing the viscosity and strength of the coating, but also having hiding power, adhesion and bonding force, so that each component is evenly dispersed, and the coating is tightly bonded to the steel plate substrate; modified glass fiber can enhance the hardness, wear resistance, strength and bonding force of the coating, so that the coating has excellent heat resistance, impact resistance and crack resistance; microcrystalline wax powder improves the scratch resistance and wear resistance of the coating; modified glass fiber is loaded on the surface and pores of modified bentonite, increasing the specific surface area of modified bentonite, and microcrystalline wax powder has a certain viscosity, which can increase the connectivity between modified glass fiber and modified bentonite, thereby increasing the structural stability of the system, which is helpful to subsequently improve the mechanical properties, adhesion and wear resistance of the coating.
[0011] Preferably, the mass ratio of the modified bentonite, the modified glass fiber and the microcrystalline wax powder is 0.8-1.2:1:2-2.5.
[0012] By adopting the above technical scheme, the mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder is further limited within a certain range, so as to obtain a wrinkle coating with excellent mechanical properties, good wear resistance and good adhesion. The modified glass fiber is loaded on the surface of the modified bentonite, and the microcrystalline wax powder can coat the modified bentonite and the modified glass fiber, so that the modified bentonite and the modified glass fiber are more tightly connected, thereby increasing the mechanical properties of the modified bentonite, which is subsequently applied to the wrinkle coating to increase the corresponding performance of the coating.
[0013] Preferably, the preparation method of the modified bentonite comprises the following steps:
[0014] (1) crushing bentonite, heating at a temperature of 250-300° C. for 2-5 hours, then dispersing in an aqueous solution of sodium hexametaphosphate, stirring for 1-2 hours, filtering, washing with water, and drying to obtain treated bentonite;
[0015] (2) dispersing lignin in hydrogen peroxide, stirring for 1-2 hours, washing with water, and then dispersing the lignin in deionized water, adding a silane coupling agent, stirring at a temperature of 80-85° C. for 1-3 hours, filtering, and drying to obtain treated lignin;
[0016] (3) Dispersing the bentonite treated in step (1) in deionized water, adding the lignin treated in step (2), stirring at a temperature of 60-65° C. for 2-3 h, filtering, and drying to obtain modified bentonite.
[0017] By adopting the above technical scheme, bentonite has good mechanical properties, wear resistance and adhesion. The bentonite is heated at 250-300°C for calcination to evaporate the moisture in the bentonite and remove impurities between the pores, thereby enhancing the adsorption performance of the bentonite and changing the microstructure of the bentonite. The layered structure of montmorillonite is made looser, thereby increasing the specific surface area of the bentonite. It is then mixed with an aqueous solution of sodium hexametaphosphate to further improve the expansion and dispersibility of the bentonite, which is helpful for the subsequent mixing of the bentonite with other components.
[0018] Lignin has the advantages of durability, flame retardancy, corrosion resistance, and water resistance. Hydrogen peroxide erodes lignin to a certain extent, increasing the specific surface area of lignin. When a silane coupling agent is added, the active groups of lignin and the groups of the silane coupling agent undergo chemical cross-linking, increasing the structural tightness between lignins, improving the interfacial compatibility of lignin in the system, and facilitating the subsequent mixing of lignin with various components.
[0019] The treated bentonite and treated lignin are mixed, and the lignin is loaded on the surface of the bentonite. At the same time, the silane coupling agent bonds with the silanol groups on the surface of the bentonite, thereby increasing the specific surface area of the bentonite. The bentonite, lignin and silane coupling agent form a cross-linked network structure, thereby improving the mechanical properties and wear resistance of the bentonite. The subsequent application in wrinkle coatings improves the adhesion and wear resistance of the coatings, making the coatings more durable and stable.
[0020] Preferably, the mass ratio of the bentonite, lignin and silane coupling agent is 1:0.5-0.8:0.03-0.06.
[0021] By adopting the above technical scheme, the mass ratio of bentonite, lignin and silane coupling agent is further limited within a certain range, and a modified bentonite with excellent mechanical properties, good wear resistance and good adhesion is obtained. Lignin is loaded on the surface of bentonite, and the silane coupling agent undergoes cross-linking reactions with the active groups on lignin and bentonite respectively, so that a cross-linked network structure is formed between bentonite, lignin and silane coupling agent, thereby improving the corresponding properties of bentonite, and is subsequently applied to wrinkle coatings to improve the corresponding properties of the coatings.
[0022] Preferably, the mass ratio of the bentonite to the sodium hexametaphosphate aqueous solution is 1:25-30.
[0023] By adopting the above technical scheme, the mass ratio of bentonite to sodium hexametaphosphate aqueous solution is further limited within a certain range, so as to obtain treated bentonite with good swelling and good dispersibility. The sodium hexametaphosphate modifies the bentonite so that the bentonite forms a dispersed and dense microstructure. The sodium hexametaphosphate separates the bentonite particle agglomerates through ion exchange and chemical adsorption, so as to obtain treated bentonite with higher swelling and good dispersibility.
[0024] Preferably, the method for preparing the modified glass fiber comprises the following steps:
[0025] (1) soaking the glass fiber in an acetone solution, stirring for 2-3 hours, washing with water, filtering, and drying, and then dispersing the glass fiber in a nitric acid solution, stirring for 1-2 hours, washing with water, filtering, and drying to obtain a treated glass fiber;
[0026] (2) calcining the nano-silicon dioxide at a temperature of 300-350° C. for 2-3 hours, grinding, dispersing in deionized water, filtering, and drying to obtain treated nano-silicon dioxide;
[0027] (3) Dispersing the glass fiber treated in step (1) in acetone, then adding the nano-silica treated in step (2), and then adding polyacrylate, stirring at a temperature of 60-65° C. for 2-3 hours to obtain modified glass fiber.
[0028] By adopting the above technical solution, the glass fiber has good mechanical strength, but poor wear resistance. The glass fiber is treated with acetone to remove organic impurities on the surface of the glass fiber, and then the nitric acid is used to strip the glass fiber to a certain extent, so that the surface of the glass fiber becomes porous, thereby increasing the specific surface area and wear resistance of the glass fiber.
[0029] Nano-silica has good wear resistance, strength, toughness, mechanical properties and anti-aging properties. Nano-silica is calcined to remove organic impurities on its surface, increase the crystallinity of nano-silica, and then the treated glass fiber and nano-silica are dispersed in acetone, and the nano-silica is loaded on the surface and pores of the glass fiber, which increases the mechanical strength, wear resistance and toughness of the glass fiber. Polyacrylate is then added. Polyacrylate has certain viscosity and film-forming properties, can coat the glass fiber and nano-silica, and increase the adhesion between the glass fiber and the nano-silica, thereby obtaining glass fiber with stable comprehensive properties, which is subsequently applied to wrinkle coatings to improve the mechanical properties and wear resistance of the wrinkle coatings.
[0030] Preferably, the mass ratio of the glass fiber, nano-silicon dioxide and polyacrylate is 1:0.2-0.6:0.01-0.03.
[0031] By adopting the above technical scheme, the mass ratio of glass fiber, nano-silica and polyacrylate is further limited within a certain range, so as to obtain glass fiber with good mechanical properties and good wear resistance. Nano-silica is loaded on the surface and pores of the glass fiber, and polyacrylate increases the viscosity between nano-silica and glass fiber, thereby improving the mechanical properties and wear resistance of the glass fiber, which is subsequently applied to wrinkle coatings to improve the corresponding properties of the coatings.
[0032] Preferably, the glass fiber has a diameter of 1-5 μm and a length of 0.3-0.6 mm.
[0033] By adopting the above technical solution, the diameter and length of the glass fiber are further limited, and glass fiber with high tensile strength, good heat resistance and excellent corrosion resistance is obtained.
[0034] Preferably, the pigment includes one or more of iron yellow, iron red, pigment green and carbon black.
[0035] By adopting the above technical solution, the pigment is not only decorative, but also increases the paint film strength of the paint, and improves the viscosity, adhesion, weather resistance and corrosion resistance of the paint.
[0036] In a second aspect, the present application also provides a method for preparing a corrugated stainless steel color-coated plate, comprising the following steps:
[0037] The polyester resin, titanium dioxide, wrinkle agent, rosin resin, modified bentonite, modified glass fiber, triglycidyl isocyanurate, microcrystalline wax powder and pigment are mixed, stirred at a temperature of 70-80°C for 20-30 minutes, then melt-extruded and granulated, and the granulated product is crushed and sieved to obtain a wrinkle coating; then the wrinkle coating is coated on a steel plate substrate to obtain a wrinkle stainless steel color-coated plate.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. The polyester resin in the present application has good mechanical properties, excellent wear resistance, heat resistance, weather resistance and chemical resistance, titanium dioxide has good chemical stability, light stability, wear resistance and resilience, and can improve the hiding power, durability, hardness and wear resistance of the coating. The wrinkle agent is an auxiliary agent that changes the surface tension of the molten coating when the coating is melt-leveled and solidified into a film, so that the coating shrinks and produces wrinkles or orange peels; rosin resin can increase the viscosity, flexibility and wear resistance of the coating, prevent the coating from falling off and peeling during use, and increase the durability of the coating; triglycidyl isocyanurate can effectively accelerate the drying speed of the coating, increase the curing time of the coating, and make the coating and the steel plate substrate bond better.
[0040] 2. The modified bentonite in the present application can improve the suspension stability of the coating system, which not only increases the viscosity and strength of the coating, but also has hiding power, adhesion and bonding power, so that each component is evenly dispersed, and the coating is tightly bonded to the steel plate substrate; the modified glass fiber can enhance the hardness, wear resistance, strength and bonding force of the coating, so that the coating has excellent heat resistance, impact resistance and crack resistance; the microcrystalline wax powder improves the scratch resistance and abrasion resistance of the coating.
[0041] 3. In the present application, the modified glass fiber is loaded on the surface and pores of the modified bentonite, which increases the specific surface area of the modified bentonite. The microcrystalline wax powder has a certain viscosity, which can increase the connectivity between the modified glass fiber and the modified bentonite, thereby increasing the structural stability of the system, which is helpful for the subsequent improvement of the mechanical properties, adhesion and wear resistance of the coating. DETAILED DESCRIPTION
[0042] The present application is further described in detail below with reference to the embodiments.
[0043] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0044] Preparation example of modified bentonite
[0045] Preparation Example 1-1
[0046] The preparation method of modified bentonite comprises the following steps:
[0047] (1) 1.2 kg of bentonite was crushed, heated at 280° C. for 4 h, and then dispersed in 3 L of an 8% sodium hexametaphosphate aqueous solution, stirred for 2 h, filtered, washed with water, and dried to obtain treated bentonite;
[0048] (2) dispersing the lignin in 2L of hydrogen peroxide with a mass concentration of 0.5%, stirring for 2h, washing with water, and then dispersing the lignin in 3L of deionized water, adding a silane coupling agent, stirring at a temperature of 85°C for 3h, filtering, and drying to obtain treated lignin;
[0049] (3) Dispersing the bentonite treated in step (1) in 3.5 L of deionized water, adding the lignin treated in step (2), stirring at 65 ° C for 3 h, filtering and drying to obtain modified bentonite; wherein the mass ratio of bentonite, lignin and silane coupling agent is 1:0.5:0.03; and the mass ratio of bentonite to sodium hexametaphosphate aqueous solution is 1:30.
[0050] Preparation Example 1-2
[0051] The difference from Preparation Example 1-1 is that no sodium hexametaphosphate aqueous solution was added.
[0052] Preparation Example 1-3
[0053] The difference from Preparation Example 1-1 is that no lignin was added.
[0054] Preparation Example 1-4
[0055] The difference from Preparation Example 1-1 is that no silane coupling agent is added.
[0056] Preparation Example 1-5
[0057] The difference from Preparation Example 1-1 is that the mass ratio of bentonite, lignin and silane coupling agent is 1:0.8:0.06; the mass ratio of bentonite to sodium hexametaphosphate aqueous solution is 1:25.
[0058] Preparation Example 1-6
[0059] The difference from Preparation Example 1-1 is that the mass ratio of bentonite, lignin and silane coupling agent is 1:0.1:0.09.
[0060] Preparation example of modified glass fiber
[0061] Preparation Example 2-1
[0062] The preparation method of modified glass fiber comprises the following steps:
[0063] (1) 2.3 kg of glass fiber was immersed in 3.5 L of acetone solution, stirred for 3 h, washed with water, filtered, and dried, and then dispersed in 3.6 L of 20% nitric acid solution, stirred for 2 h, washed with water, filtered, and dried to obtain treated glass fiber;
[0064] (2) calcining the nano-silicon dioxide at a temperature of 330° C. for 3 h, grinding it, and then dispersing it in 5 L of deionized water, filtering it, and drying it to obtain treated nano-silicon dioxide;
[0065] (3) dispersing the glass fiber treated in step (1) in 3.5 L of acetone, then adding the nano-silica treated in step (2), and then adding polyacrylate, stirring at a temperature of 65° C. for 3 h to obtain modified glass fiber; wherein the mass ratio of the glass fiber, the nano-silica and the polyacrylate is 1:0.6:0.01; the diameter of the glass fiber is 1-5 μm, and the length is 0.3-0.6 mm.
[0066] Preparation Example 2-2
[0067] The difference from Preparation Example 2-1 is that no nano-silicon dioxide is added.
[0068] Preparation Example 2-3
[0069] The difference from Preparation Example 2-1 is that no polyacrylate was added.
[0070] Preparation Example 2-4
[0071] The difference from Preparation Example 2-1 is that the mass ratio of glass fiber, nano-silica and polyacrylate is 1:0.2:0.03.
[0072] Preparation Example 2-5
[0073] The difference from Preparation Example 2-1 is that the mass ratio of glass fiber, nano-silica and polyacrylate is 1:0.9:0.05.
[0074] Example
[0075] Example 1
[0076] A wrinkle stainless steel color-coated plate comprises a steel plate substrate and a wrinkle coating, wherein the wrinkle coating comprises the following raw materials by weight: 40 kg of polyester resin, 12 kg of titanium dioxide, 1 kg of wrinkle agent, 3 kg of rosin resin, 10 kg of modified bentonite, 8 kg of modified glass fiber, 10 kg of triglycidyl isocyanurate, 30 kg of microcrystalline wax powder and 1 kg of pigment; the model of the wrinkle agent is TP301.
[0077] The polyester resin was purchased from Guangdong Sanqi New Materials Co., Ltd., the model is Lankelu L-6127; the pigment is iron yellow.
[0078] The modified bentonite was prepared according to Preparation Example 1-1; the modified glass fiber was prepared according to Preparation Example 2-1.
[0079] The method for preparing the above-mentioned corrugated stainless steel color-coated sheet is characterized by comprising the following steps:
[0080] The polyester resin, titanium dioxide, wrinkle agent, rosin resin, modified bentonite, modified glass fiber, triglycidyl isocyanurate, microcrystalline wax powder and pigment are mixed, stirred at a temperature of 75°C for 25 minutes, then melt-extruded and granulated, the granulated product is crushed and passed through a 100-mesh sieve to obtain a wrinkle coating; then the wrinkle coating is coated on a steel plate substrate to obtain a wrinkle stainless steel color-coated plate.
[0081] The wrinkle coating was sprayed on a steel plate substrate by an electrostatic spraying construction method, with a coating thickness of 40 μm, and then baked and cured at 185° C. for 20 minutes, and naturally cooled to room temperature to obtain a wrinkle stainless steel color-coated plate.
[0082] The extruder barrel temperature was 115°C, the extruder screw temperature was 85°C, and the extruder speed was 80 rpm.
[0083] Example 2
[0084] A wrinkle stainless steel color-coated plate, which is different from Example 1 in that the wrinkle coating comprises the following raw materials by weight: 50 kg of polyester resin, 20 kg of titanium dioxide, 3 kg of wrinkle agent, 5 kg of rosin resin, 15 kg of modified bentonite, 15 kg of modified glass fiber, 6 kg of triglycidyl isocyanurate, 20 kg of microcrystalline wax powder and 2 kg of pigment.
[0085] Example 3
[0086] A corrugated stainless steel color-coated plate is different from Example 1 in that the mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder is 1:1:2.2.
[0087] Example 4
[0088] A corrugated stainless steel color-coated plate is different from Example 1 in that the mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder is 0.8:1:2.
[0089] Example 5
[0090] A corrugated stainless steel color-coated plate is different from Example 1 in that the mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder is 1.2:1:2.5.
[0091] Example 6
[0092] A corrugated stainless steel color-coated plate, which is different from Example 1 in that the modified bentonite is prepared according to Preparation Example 1-2.
[0093] Example 7
[0094] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified bentonite is prepared according to Preparation Examples 1-3.
[0095] Example 8
[0096] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified bentonite is prepared according to Preparation Examples 1-4.
[0097] Example 9
[0098] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified bentonite is prepared according to Preparation Examples 1-5.
[0099] Example 10
[0100] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified bentonite is prepared according to Preparation Examples 1-6.
[0101] Embodiment 11
[0102] A corrugated stainless steel color-coated plate, which is different from Example 1 in that the modified glass fiber is prepared according to Preparation Example 2-2.
[0103] Example 12
[0104] A corrugated stainless steel color-coated plate, which is different from Example 1 in that the modified glass fiber is prepared according to Preparation Example 2-3.
[0105] Embodiment 13
[0106] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified glass fiber is prepared according to Preparation Examples 2-4.
[0107] Embodiment 14
[0108] A corrugated stainless steel color-coated plate is different from Example 1 in that the modified glass fiber is prepared according to Preparation Examples 2-5.
[0109] Comparative Example
[0110] Comparative Example 1
[0111] A corrugated stainless steel color-coated plate, which differs from Example 1 in that modified bentonite is not added.
[0112] Comparative Example 2
[0113] A corrugated stainless steel color-coated plate is different from Example 1 in that an equal amount of bentonite is used instead of modified bentonite.
[0114] Comparative Example 3
[0115] A corrugated stainless steel color-coated plate, which differs from Example 1 in that no modified glass fiber is added.
[0116] Comparative Example 4
[0117] A corrugated stainless steel color-coated plate is different from Example 1 in that an equal amount of glass fiber is used to replace the modified glass fiber.
[0118] Comparative Example 5
[0119] A corrugated stainless steel color-coated plate, which differs from Example 1 in that no microcrystalline wax powder is added.
[0120] Performance testing
[0121] The performance of the corrugated stainless steel color-coated plates prepared in Examples 1-14 and Comparative Examples 1-5 was tested. The test standards are shown below and the test results are shown in Table 1.
[0122] Table 1 Tests of Examples and Comparative Examples
[0123]
[0124]
[0125] The wrinkled stainless steel color-coated plates prepared in Examples 1-5, 9 and 13 of the present application have good adhesion, mechanical properties, wear resistance and salt spray resistance. Among them, the adhesion of Example 3 is level 0, the pencil hardness is 5H, the impact is 59.7kg﹒cm, the wear resistance value is 29, and the salt spray resistance test of 10000h is passed. According to the impact and wear resistance tests, it can be seen that the numerical test ranking of Examples 1-5 is the best, followed by Examples 4-5, and the worst of Examples 1-2. Among them, Example 3 is the optimal mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder. By comparison, it is found that the modified bentonite, modified glass fiber and microcrystalline wax powder have a synergistic effect. When the mass ratio of modified bentonite, modified glass fiber and microcrystalline wax powder is within a certain range, the wrinkle coating has better comprehensive performance.
[0126] In the preparation method of modified bentonite in Example 6, no sodium hexametaphosphate aqueous solution is added. As can be seen from Table 1, the adhesion is level 0, the pencil hardness is 5H, the impact resistance is 57.2kg﹒cm, the wear resistance value is 24, and the salt spray resistance 10000h test is passed, indicating that sodium hexametaphosphate modified bentonite, so that the bentonite forms a dispersed and dense microstructure, separates the bentonite particle agglomerates, and obtains a treated bentonite with higher expansibility and good dispersibility, which is helpful for the subsequent modification of bentonite, and then modifies the comprehensive performance of the wrinkle coating.
[0127] In the preparation method of modified bentonite in Example 7, no lignin is added. As can be seen from Table 1, the adhesion is level 0, the pencil hardness is 4H, the impact is 52.3kg﹒cm, the wear resistance value is 29, and the salt spray resistance is 9000h, indicating that the active groups of lignin and the groups of the silane coupling agent are chemically cross-linked, which increases the structural tightness between lignins and improves the interfacial compatibility of lignin in the system, which is conducive to the subsequent mixing of lignin with various components, thereby affecting the corresponding properties of the modified bentonite.
[0128] In Example 8, no silane coupling agent is added to the modified bentonite. As can be seen from Table 1, the adhesion is level 1, the pencil hardness is 4H, the impact resistance is 52.6kg﹒cm, the abrasion resistance value is 28, and the salt spray resistance performance passes 10000h, indicating that the silane coupling agent can react with lignin and bentonite, thereby improving the performance of bentonite, which is helpful to subsequently improve the relevant properties of the wrinkle coating.
[0129] Example 10 changes the mass ratio of bentonite, lignin and silane coupling agent. As can be seen from Table 1, the impact resistance and wear resistance test values are better than those of Examples 7-8, but worse than those of Examples 1-5 and Example 9, indicating that there is a synergistic effect between bentonite, lignin and silane coupling agent. Lignin is loaded on the surface of bentonite, and the silane coupling agent undergoes cross-linking reaction with the active groups on lignin and bentonite, respectively, so that a cross-linked network structure is formed between bentonite, lignin and silane coupling agent, thereby improving the corresponding properties of bentonite, and improving the corresponding properties of the coating in the subsequent application in wrinkle coatings.
[0130] In the preparation method of modified glass fiber of Example 11, nano-silicon dioxide is not added. As can be seen from Table 1, the adhesion is level 0, the pencil hardness is 3H, the impact resistance is 50.1kg﹒cm, the wear resistance value is 32, and the salt spray resistance is 8000h, indicating that nano-silicon dioxide has good wear resistance, strength, toughness, mechanical properties and anti-aging properties. Nano-silicon dioxide can be loaded on the surface and pores of glass fiber, thereby improving the corresponding properties of glass fiber.
[0131] In the preparation method of modified glass fiber in Example 12, no polyacrylate is added. As can be seen from Table 1, the adhesion is level 1, the pencil hardness is 5H, the impact resistance is 51.2kg﹒cm, the wear resistance value is 31, and the salt spray resistance is 9000h, indicating that polyacrylate has certain viscosity and film-forming properties, can coat glass fiber and nano-silica, increase the adhesion between glass fiber and nano-silica, and thus obtain glass fiber with stable comprehensive performance, and then modify the relevant properties of wrinkle coatings.
[0132] Example 14 changes the mass ratio of glass fiber, nano-silica and polyacrylate. As can be seen from Table 1, the impact resistance and wear resistance test values are better than those of Examples 11-12, but worse than those of Examples 1-5 and Example 13, indicating that there is a synergistic effect between the glass fiber, nano-silica and polyacrylate. The nano-silica is loaded on the surface and pores of the glass fiber, and the polyacrylate increases the viscosity between the nano-silica and the glass fiber, thereby improving the mechanical properties and wear resistance of the glass fiber. It is subsequently applied to wrinkle coatings to improve the corresponding properties of the coatings.
[0133] Comparative Example 1: No modified bentonite is added to the raw materials of the wrinkled stainless steel color-coated plate. As can be seen from Table 1, the adhesion is level 3, the pencil hardness is 2H, the impact is 45.1kg﹒cm, the wear resistance value is 37, and the salt spray resistance is 8000h, which shows that the modified bentonite can improve the suspension stability of the coating system, not only increase the viscosity and strength of the coating, but also have hiding power, adhesion and bonding force, so that each component is evenly dispersed, so that the coating and the steel plate substrate are closely bonded, and then the relevant properties of the subsequent modified wrinkle coating are improved.
[0134] Comparative Example 2: In the raw material of the wrinkled stainless steel color-coated plate, an equal amount of bentonite is used instead of the modified bentonite. As can be seen from Table 1, the adhesion is level 1, the pencil hardness is 3H, the impact is 47.1kg﹒cm, the wear resistance value is 35, and the salt spray resistance is 8500h, indicating that the modified bentonite prepared in this application has excellent mechanical properties, wear resistance and adhesion, and is subsequently applied to wrinkle coatings to further modify the relevant properties of the coatings.
[0135] Comparative Example 3: No modified glass fiber is added to the raw material of the wrinkled stainless steel color-coated plate. As can be seen from Table 1, the adhesion is level 2, the pencil hardness is 1H, the impact is 42.3kg﹒cm, the wear resistance value is 38, and the salt spray resistance is 7000h, indicating that the modified glass fiber can enhance the hardness, wear resistance, strength and adhesion of the coating, so that the coating has excellent heat resistance, impact resistance and crack resistance, and is subsequently added to the wrinkled coating to increase the corresponding performance of the coating.
[0136] Comparative Example 4: In the raw material of the corrugated stainless steel color-coated plate, an equal amount of glass fiber is used instead of the modified glass fiber. As can be seen from Table 1, the adhesion is level 1, the pencil hardness is 2H, the impact is 43.2kg﹒cm, the wear resistance value is 36, and the salt spray resistance is 8000h, indicating that the modified glass fiber prepared in this application has excellent mechanical strength and wear resistance, and is subsequently applied to the wrinkle coating to improve the corresponding performance of the modified coating.
[0137] Comparative Example 5 No microcrystalline wax powder is added to the raw materials of the wrinkled stainless steel color-coated plate. As can be seen from Table 1, the adhesion is level 3, the pencil hardness is 4H, the impact is 49.2kg﹒cm, the wear resistance value is 33, and the salt spray resistance is 9000h, indicating that the microcrystalline wax powder has a certain viscosity, which can increase the connectivity between the modified glass fiber and the modified bentonite, thereby increasing the structural stability of the system, which is helpful to subsequently improve the mechanical properties, adhesion and wear resistance of the wrinkle coating.
[0138] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A corrugated stainless steel color-coated plate, characterized in that: The invention comprises a steel plate substrate and a wrinkle coating, wherein the wrinkle coating comprises the following raw materials in parts by weight: 40-50 parts of polyester resin, 12-20 parts of titanium dioxide, 1-3 parts of wrinkle agent, 3-5 parts of rosin resin, 10-15 parts of modified bentonite, 8-15 parts of modified glass fiber, 6-10 parts of triglycidyl isocyanurate, 20-30 parts of microcrystalline wax powder and 1-2 parts of pigment; The preparation method of the modified bentonite comprises the following steps: (1) crushing bentonite, heating it at a temperature of 250-300° C. for 2-5 hours, then dispersing it in an aqueous solution of sodium hexametaphosphate, stirring it for 1-2 hours, filtering it, washing it with water, and drying it to obtain treated bentonite; (2) dispersing lignin in hydrogen peroxide, stirring for 1-2 hours, washing with water, and then dispersing lignin in deionized water, adding a silane coupling agent, stirring at a temperature of 80-85°C for 1-3 hours, filtering, and drying to obtain treated lignin; (3) dispersing the bentonite treated in step (1) in deionized water, adding the lignin treated in step (2), stirring at a temperature of 60-65° C. for 2-3 h, filtering, and drying to obtain modified bentonite; The method for preparing the modified glass fiber comprises the following steps: (1) Soaking the glass fiber in an acetone solution, stirring for 2-3 hours, washing with water, filtering, and drying, and then dispersing it in a nitric acid solution, stirring for 1-2 hours, washing with water, filtering, and drying to obtain treated glass fiber; (2) calcining the nano-silicon dioxide at a temperature of 300-350° C. for 2-3 hours, grinding, then dispersing in deionized water, filtering, and drying to obtain treated nano-silicon dioxide; (3) Dispersing the glass fiber treated in step (1) in acetone, then adding the nano-silica treated in step (2), and then adding polyacrylate, stirring at a temperature of 60-65° C. for 2-3 hours to obtain modified glass fiber.
2. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The mass ratio of the modified bentonite, the modified glass fiber and the microcrystalline wax powder is 0.8-1.2:1:2-2.
5.
3. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The mass ratio of the bentonite, lignin and silane coupling agent is 1:0.5-0.8:0.03-0.
06.
4. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The mass ratio of the bentonite to the sodium hexametaphosphate aqueous solution is 1:25-30.
5. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The mass ratio of the glass fiber, nano silicon dioxide and polyacrylate is 1:0.2-0.6:0.01-0.
03.
6. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The glass fiber has a diameter of 1-5 μm and a length of 0.3-0.6 mm.
7. The corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The pigment includes one or more of iron yellow, iron red, pigment green and carbon black.
8. The method for preparing a corrugated stainless steel color-coated sheet according to claim 1, characterized in that: The method comprises the following steps: mixing polyester resin, titanium dioxide, wrinkle agent, rosin resin, modified bentonite, modified glass fiber, triglycidyl isocyanurate, microcrystalline wax powder and pigment, stirring at a temperature of 70-80°C for 20-30 minutes, then melt-extruding, granulating, crushing and sieving the granulated product to obtain wrinkle coating; and then coating the wrinkle coating on a steel plate substrate to obtain a wrinkle stainless steel color-coated plate.
Citation Information
Patent Citations
Water-resistant-type water-based polyurethane ink containing modified bentonite and preparation method of water-resistant-type water-based polyurethane ink
CN105885530A
High-temperature-resistant coating liquid used for thermal transfer paper
CN108192425A